In vitro Antimalarial Activity of Novel Trifluoromethyl- and Bis(trifluoro-methyl) quinoline Derivatives - Kgokong, Joseph L.; Matsabisa, Gilbert M.; Breytenbach, Jaco C. (Arzneimittelforschung, 2001)
The in vitro antimalarial activity of a series of 2 and 8 trifluoromethyl and 2,8- bis (trifluoromethyl)quinoline 4 -(5 -pyrimidino) and N4- ethyl -5- nitroimidazolo) methylene ketones was assessed against the chloroquine sensitive strain (D10) of Plasmodium falciparum. Although the in vitro antimalarial activity of these compounds is more or less of the same order of magnitude, derivatives containing two trifluoromethyl groups achieve a slightly higher in vitro activity than compounds with one trifluoromethyl group, with 2,8 bis (trifluoromethyl) quinoline 4 (N4 ethyl 5 nitroimidazolo) methylene and 2,8 bis (trifluoromethyl) quinoline 4 (5 pyrimidino) ketones showing IC50 of 4,8 and 5,2µg/ml, respectively. These compounds seem to bind to DNA by intercalation.
Keywords: Antimalarial drugs; Trifluoromethylquinoline derivatives, DNA intercalation, in vitro antimalarial activity